2018
DOI: 10.3758/s13415-018-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Age of avatar modulates the altercentric bias in a visual perspective-taking task: ERP and behavioral evidence

Abstract: Despite being able to rapidly and accurately infer their own and other peoples’ visual perspectives, healthy adults experience difficulty ignoring the irrelevant perspective when the two perspectives are in conflict; they experience egocentric and altercentric interference. We examine for the first time how the age of an observed person (adult vs. child avatar) influences adults’ visual perspective-taking, particularly the degree to which they experience interference from their own or the other person’s perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 75 publications
2
39
1
Order By: Relevance
“…More recently, a number of studies replicated and extended the results of , which led to the conclusion that visual perspective taking is indeed an automatic process in humans (see Qureshi et al, 2010;Nielsen et al, 2015;Ferguson et al, 2017Ferguson et al, , 2018Furlanetto et al, 2016;Simpson et al, 2017). The altercentric interference observed in these studies has been interpreted as evidence that the mere presence of an avatar automatically triggers perspective taking (Surtees et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…More recently, a number of studies replicated and extended the results of , which led to the conclusion that visual perspective taking is indeed an automatic process in humans (see Qureshi et al, 2010;Nielsen et al, 2015;Ferguson et al, 2017Ferguson et al, , 2018Furlanetto et al, 2016;Simpson et al, 2017). The altercentric interference observed in these studies has been interpreted as evidence that the mere presence of an avatar automatically triggers perspective taking (Surtees et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…First, studies have demonstrated that the realism of avatars is important for understanding human behaviour. Experiments on visual perspective taking, for example, show that humanness and the correspondence between avatar and participant affect interpretation of what the avatar can see (Ferguson et al, 2018;Nielsen et al, 2015). Second, by following our avatar construction method, it is possible to import avatars of real people into VR.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, our avatars also hold broader application beyond that of face perception. For example, our avatar construction method could be used to generate useful stimuli for social psychological questions that can be explored in VR using avatars (see, e.g., Kane et al, 2012;Skulmowski et al, 2014;Slater & Steed, 1999), as well as cognitive studies in which the participant must simulate the visual perspective of somebody else (see, e.g., Begeer et al, 2010;Ferguson et al, 2018). Likewise, clinical research studies are increasingly utilising VR to enhance the real-world application of assessment tools (Bell et al, 2020), within which avatars already represent a key component (Mölbert et al, 2018;Powers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another example of the shift between egocentricism and altercentrism is evident in the dot-perspective taking task where, if there exists a conflict in perspectives, participants are faster to judge the selfperspective (suggesting an egocentric bias) but if there is no conflict, participants are faster to judge the other's perspective (suggesting an altercentric bias) [56,156]. Egocentric interference, overall, tends to be more pronounced than altercentric interference but both effects appear to increase with more perceived similarity between self and other: egocentric interference is larger for in-group than for out-group members [157], and altercentric effects are reduced when the other differs in age from the respondent [158].…”
Section: Box 4: Egocentric Vs Altercentric Cognitionmentioning
confidence: 97%